PELAKSANAAN PROGRAM BANTUAN LANGSUNG TUNAI (BLT) DANA DESA DI DESA JALUR PATAH KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2020 - Guslan, Fero Alfharizi; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Direct Cash Assistance (BLT) Village Fund is a draft activity issued by the Indonesian government which aims to overcome the economic poverty of people affected by the Covid-19 Pandemic. The assistance is in the form of finances provided to poor people and families affected by the Covid-19 pandemic. This study aims to determine how the implementation of the Village Fund Direct Cash Assistance (BLT) Program in Jalur Patah Village, Sentajo Raya District, Kuantan Singingi Regency and at the same time to find out what are the constraints in the implementation of the Village Fund Direct Cash Assistance (BLT) Program. This study uses the Pratiwi & Hayati Theory which has three indicators to achieve the objectives (Preparation, Program Implementation, Accountability and Reporting). In order to answer these problems, the researcher uses a descriptive qualitative approach. The results of this study are in the Implementation of the Direct Cash Assistance Program (BLT) Village Funds in Jalur Patah Village, Sentajo Raya District, Kuantan Singingi Regency, it has not been running well. The Village Government is not optimal in its duties in collecting data on the criteria for recipients of Direct Cash Assistance (BLT) Village Funds so that there are still many names of people who have not been recorded for receiving Direct Cash Assistance (BLT) Village Funds. For this reason, it is hoped that the Village Government will issue a policy before issuing a policy. Keywords: Preparation, Program Implementation, Accountability and Reporting